براہوئی خلکی شیئرباگل آتیٹی پہوالی زندنا دروشم: Reflection of Nomadic Life in Brahui Folk Lore - Lehri, Inayatullah; sarpra, Hafeez ullah; Naz, Ghulam Hyder; Bano, Noureen (Al-Burz, 2014)
The main objective of this article displays the background of Brahui folk music which tells thousand years historical prospective of nomadic life style and the development of their musical skills. Their honesty and affections natural beauty with complete source of information. The importance, impacts, necessity and values which portrays the basics of nomadic life. These all are composed of social life, living standards, sorrows and happiness, family and groups, tent (Gidán), migration and encampment, love and affection, patriotism, mother land and abroad, herd of camels and sheep, agriculture and farming, changing of weathers, characters, beliefs and ethics, hospitality and honesty, health and illness, entertainment, hardworking, brevity and cowardice. Include all these the protection of mother tongue is displayed in nomadic living style and respect of each individual sentiment in the Brahui folk music. In this context disciplinary code of life can be clearly imagined. The Brahui folk music visualizes the complete background of nomadic life with melodies.